2006
DOI: 10.1016/j.yhbeh.2005.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic estradiol treatments reduce memory deficits induced by transient global ischemia in female rats

Abstract: Transient global ischemia induces selective, delayed neuronal death in the hippocampal CA1 and delayed cognitive deficits. Estrogen treatment ameliorates hippocampal injury associated with global ischemia. Although much is known about the impact of estrogen on neuronal survival, relatively little is known about its impact on functional outcome assessed behaviorally. We investigated whether long-term estradiol (21-day pellets implanted 14 days prior to ischemia) or acute estradiol (50 microg infused into the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
3
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 83 publications
8
77
3
1
Order By: Relevance
“…After ischemia, an increase in spine turnover is observed (29), as is an increase in E2 synthesis (30), which is suggestive of a putative natural recovery mechanism. Animal models of stroke have demonstrated that E2 treatment after ischemic insult significantly improves cortical memory normally disrupted by ischemia (31). It is intriguing to speculate that E2-induced wiring plasticity may in part underlie this recovery and that this mechanism of increased connectivity may be exploited to aid in the recovery from cortical dysfunction induced by brain injury.…”
Section: Combined Rap and Rac Signaling: A Possible Mechanism For Wiringmentioning
confidence: 99%
“…After ischemia, an increase in spine turnover is observed (29), as is an increase in E2 synthesis (30), which is suggestive of a putative natural recovery mechanism. Animal models of stroke have demonstrated that E2 treatment after ischemic insult significantly improves cortical memory normally disrupted by ischemia (31). It is intriguing to speculate that E2-induced wiring plasticity may in part underlie this recovery and that this mechanism of increased connectivity may be exploited to aid in the recovery from cortical dysfunction induced by brain injury.…”
Section: Combined Rap and Rac Signaling: A Possible Mechanism For Wiringmentioning
confidence: 99%
“…This hypothesis is also consistent with a role for both CA1 and septum in memory performance. Lesions to the CA1 significantly impair performance on OR and OP tasks (Broadbent et al, 2004;Gulinello et al, 2006); OP in particular is dependent on an intact hippocampus and/or fornix (Ennaceur and Aggleton, 1994;Ennaceur et al, 1997;Mumby et al, 2002;Broadbent et al, 2004). Similarly, lesions to the dorsal hippocampus (containing CA1 and septal regions) impair performance on the Morris water maze to the same extent as lesions of whole hippocampus (Clark et al, 2005).…”
Section: Multiparity Significantly Elevated Bdnf Concentration In Ca1mentioning
confidence: 98%
“…12-14 Although most of these animal studies emphasized infarct size and cell loss early after the insult, chronic estrogen supplementation also improved functional outcome. 15, 16 The effects of chronic estrogen exposure in these models may explain some of the female advantage in IBI, and they are the focus of recent studies in primary stroke prevention. However, since long-term treatment before a perioperative brain insult is obviously not an option for neuroprotection, the efficacy of acute treatment with estrogen in the perioperative setting at or after onset of ischemia has also been tested in experimental ischemia and found to reduce brain damage.…”
Section: Estrogen and Ibi: What We Know From The Benchmentioning
confidence: 99%
“…33 This may contribute to the improved memory function outcome after ischemia that is seen in estrogensupplemented animals. 16 In classical estrogen signaling, 17β-estradiol (E2), the predominant human estrogen, binds to an estrogen receptor (ER), usually ER-α or ER-β, which translocates to the nucleus and binds to an estrogen-response element (ERE) on the target gene to activate transcription. Both ER-α and ER-β are widely expressed under physiologic conditions in all cell types throughout the brain, i.e., neurons, glia, and endothelial cells, including in ischemia-sensitive areas such as neocortex and hippocampus.…”
Section: Estrogen and Ibi: What We Know From The Benchmentioning
confidence: 99%